2004
DOI: 10.1039/b409929j
|View full text |Cite
|
Sign up to set email alerts
|

Nickel(iii) oxidation of its glycylglycylhistamine complex

Abstract: The doubly-deprotonated Ni(III) complex of Gly(2)Ha (where Ha is histamine) undergoes base-assisted oxidative self-decomposition of the peptide. At Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…A [(Ni III salen) 2 O] species has been isolated and its crystal structure determined [209]. The self-decomposition reaction of [Ni III (H Ϫ2 Gly 2 Hm)] ϩ at pH 5 to 7.0 is a two-electron oxidation at the N-terminal glycyl residue to give [Ni II (H Ϫ2 glyoxylglycylhistamine)] [210]. By contrast, the [Ni III (H Ϫ2 Gly 2 HisGly)] complex undergoes a four-electron oxidation at the same site.…”
Section: Methodsmentioning
confidence: 99%
“…A [(Ni III salen) 2 O] species has been isolated and its crystal structure determined [209]. The self-decomposition reaction of [Ni III (H Ϫ2 Gly 2 Hm)] ϩ at pH 5 to 7.0 is a two-electron oxidation at the N-terminal glycyl residue to give [Ni II (H Ϫ2 glyoxylglycylhistamine)] [210]. By contrast, the [Ni III (H Ϫ2 Gly 2 HisGly)] complex undergoes a four-electron oxidation at the same site.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is not surprising that many efforts have been devoted to developing different catalytic systems based on the coordination of pseudopeptidic ligands to different metals. [1][2][3][4] In this regard, we have recently studied the Cu 2+ and Zn 2+ coordination properties of simple C 2 symmetric pseudopeptides such as 1 (see Scheme 1) in which two valine fragments are connected by an aliphatic spacer (-(CH 2 ) n -). [5][6][7][8][9][10][11][12] Spectroscopic, mass spectrometric and X-ray crystallographic studies revealed that the corresponding complexes can adopt a variety of coordination geometries depending on several factors such as the nature of the cation, pH of the medium and the length of the central aliphatic spacer.…”
Section: Introductionmentioning
confidence: 99%
“…Stable 4N Ni(II) complexes with C-terminal reaction products may produce oxidative damage when exposed to hydrogen peroxide, which is an endogenous molecule. Such reactivity, proceeding via Ni(III) intermediates, was demonstrated for a range of synthetic complexes and for naturally occurring peptides bearing analogous N-terminal His-3 sequences [124][125][126][127]. It is very likely to contribute to molecular processes underlying Ni(II) carcinogenesis [118,119,128], and perhaps also to nickel allergy [129].…”
Section: Toxicological Implications Of Metal Assisted Peptide Bond Hymentioning
confidence: 99%